A formação de professores(as) para o atendimento educacional especializado nas escolas da Rede Estadual de São Luís - MA, no período de 2016 a 2019 - VALE, Claudia de Oliveira (2020)
This work deals with the continuing training of teachers of specialized educational care (ESA), in the schools of Basic Education, of the state public school system, in São Luís, MA, in the period from 2016 to 2019. As a General Objective, of this dissertation work, we seek to identify which continuing education theteachers of the Multifunctional Resource Rooms l(SRM),who perform their functions in the Specialized Educational Care of the State School Network ofSão Luís, receive from the Special Education Advisory(AEESP/MA) and as Specific Objectives, to map the training profile of teachers working in the AEE in the Multifunctional Resource Rooms, know the theoretical methodological proposal addressedin the continuing training aimed at teachers of the ESA, of the State Public School Network and relate these contents addressedin these continuous formations,in order to contribute to the pedagogical practice in the RMS. This research addresses Special Education, from segregated spaces in Institutes, schools or clinics that served people with disabilities, to the implementation of Multifunctional Resource Rooms. We conducted a survey on academic productions, in the scope of master's and doctorate in the last five years in the country (2013-1017). We focus on the continued training of teachers for specialized educational care, based on the theory of the reflective teacher, for this, we seek renowned authors both in Brazil and abroad. In the methodological course, we used bibliographic and field research, based on a qualitative approach and for data collection, we made questionnaires with open and closed questions with ten (10) Teachers of the ESA and with two (02) formator teachers who make up the technical team of AEESP. We also used the semi-structured interview with the Special Education Advisor of the Department of Education of the State of Maranhão. This research showed us that among the ten teachers of the ESA interviewed, only one (01) teacher invests in their self-formation and the contents addressed in this training are suggested by the teachers of the RMS themselves. Regarding initial education, 9 professors have a degree in Pedagogy and 1 (one) professor in Nursing and Biology. Of this universe of 10 teachers in this research, only one (one) teacherdoes not havea post-graduationin the area of Special Education (still in the process of completion) and 1 (one) only teacher has a master's degree in Education. To assist in the discussions about the data found and throughout the construction of the theoretical foundation, this work had the works of Alarcão (2005; 2011), Carvalho, (2010; 2015) , Costa (2011; 2012), Dourado (2015), Freire (2014), Imbérnon (2011), Lakatos (2003), Libâneo (2012), Mantoan, (2006) Mazzota (2005), Pérez (1992), Pimenta (2014), Saviani (2009), Shön (1992) Zimmermann (2018), among others.